Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 1 - Review Exercises - Page 100: 99



Work Step by Step

RECALL: (i) $a^m \cdot a^n = a^{m+n}$ (ii) $(ab)^{m} = a^mb^m$ (iii) $(a^m)^n=a^{mn}$ Use rule (ii) above to obtain: $=(-3xy^4) (2^3)(x^2)^3 \\=(-3xy^4)(8)(x^2)^3$ Use rule (iii) above to obtain: $=(-3xy^4)(8x^{2(3)}) \\=(-3xy^4)(8x^6)$ Multiply the numerical coefficients, then use rule (ii) above to obtain: $=-24x^{1+6}y^4 \\=-24x^7y^4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.